The Necessity of Early Palliative Care in Patients with Severe Coronary Artery Disease: A Reflective Practice - Adzillah, Finka Laili Nur; Haroen, Hartiah (Poltekkes Kemenkes Semarang, 2024)
Background: Palliative care aims to improve the quality of life for patients with serious illnesses and their families. It is provided throughout the course of the disease, starting from the initial diagnosis to the grieving phase after the patient's death. Coronary artery disease has been proven to be a major cause of death, making palliative care important. Purpose: This study was to reflect the patient's case in order to gain of new insight and perspective. Methods: This article was a critical review of author experience when providing patient nursing care in a hospital. The case was reviewed using reflective practice. Results: Through reflection on the case, it was found that the initiation of palliative care was only carried out when the patient was continuously deteriorating. So that patients and their families do not receive adequate palliative care. Conclusion: Early palliative care has an impact on symptoms, quality of life, and support for patients and their families during the dying process. However, there are obstacles to early palliative care implementation, such as negative stigma, medical professionals who wish to continue giving treatment in hospitals till the end, and a lack of expertise and capability among health workers to deliver palliative care.